Elastic Bands as a Component of Periodized Resistance Training. Issue 8 (August 2016) - Joy, Jordan M.; Lowery, Ryan P.; Oliveira de Souza, Eduardo; Wilson, Jacob M.
Abstract : Abstract: Joy, JM, Lowery, RP, Oliveira de Souza, E, and Wilson, JM. Elastic bands as a component of periodized resistance training. J Strength Cond Res 30(8): 2100–2106, 2016—Variable resistance training (VRT) has recently become a component of strength and conditioning programs. Prior research has demonstrated increases in power and/or strength using low loads of variable resistance. However, no study has examined using high loads of variable resistance as a part of a periodized training protocol to examine VRT within the context of a periodized training program and to examine a greater load of variable resistance than has been examined in prior research. Fourteen National Collegiate Athletic Association division II male basketball players were recruited for this study. Athletes were divided equally into either a variable resistance or control group. The variable resistance group added 30% of their 1 repetition maximum (1RM) as band tension to their prescribed weight 1 session per week. Rate of power development (RPD), peak power, strength, body composition, and vertical jump height were measured pretreatment and posttreatment. No baseline differences were observed between groups for any measurement of strength, power, or body composition. A significant group by time interaction was observed for RPD, in which RPD was greater in VRT posttraining than in the control group. Significant time effects were observed for all other variables including squat 1RM, bench press 1RM, deadlift 1RM, clean 3RM, vertical jump, and lean mass. Although there were no significant group ×-time interactions, the VRT group's percent changes and effect sizes indicate a larger treatment effect in the squat and bench press 1RM values and the vertical jump performed on the force plate and vertec. These results suggest that when using variable resistance as a component of a periodized training program, power and strength can be enhanced. Therefore, athletes who add variable resistance to 1 training session per week may enhance their athletic performance.